A concise access to bridged [2,2,1] bicyclic lactones with a quaternary stereocenter via stereospecific hydroformylation - Shuailong Li (Nature Portfolio, 2021)
Enantiomeric bridged [2,2,1] bicyclic lactone skeletons and their ring-opening products are important scaffolds widely occurring in both pharmaceutics and biology active compounds. Here the authors show an efficient method for enantioselective construction of these compounds bearing a quaternary stereocenter via Rh-catalyzed asymmetric hydroformylation/intramolecular cyclization/ pyridinium chlorochromate oxidation.